Z dokazi podprte intervencije za izboljšanje sodelovanja pri zdravljenju z zdravili - Janežič, Ana (Farmacevtski vestnik, 2015)
Medication adherence represents a major challenge as generally only half of the patients with chronic diseases adhere to their treatment. The best adherence rates can be found in HIV patients who are treated with antiretrovirals, patients with rheumatoid arthritis, gastrointestinal diseases, cancer, epilepsy and neurological diseases, and the worst adherence rates in patients with sleep disorders, diabetes, respiratory diseases, and renal failure. Patient non-adherence is often a cause of the treatment failure, so effective interventions to optimize adherence are necessary. The research focuses on a range of possible interventions with regard to potential causes of non-adherence. Technical interventions for simplification of the dosing regimen, reminders, patient education and motivation also show promising results, but complex multifaceted interventions were shown to be the most effective. However, the success of interventions largely depends on the ability to identifiy non-adherence and its underlying causes as well as tayloring the interventions to individual patients' disease-related characteristics.
Keywords: sodelovanje; zdravljenje z zdravili; intervencije; pregled uporabe zdravil; farmakoterapija